Coordination and digitalization among zakat institutions to strengthen social protection in Indonesia: an assessment of progress - Siddiq, Muhammad Rizky; Akbar, Mohamed Aslam (UTM Press, Universiti Teknologi Malaysia, 2023)
Zakat, a mandatory obligation for Muslims to disburse a portion of their wealth, has the potential to significantly alleviate poverty in Muslim-majority countries with large Muslim populations. Despite a 122% increase in zakat collection from 2015 to 2018, the national zakat collection in Indonesia remains proportionately low compared to its potential. This work intends to comprehensively elucidate on how zakat management coordination and digitalization in Indonesia have progressed to this moment. Through a content analysis of descriptive findings, the study assesses the coordination and digitalization improvement in Indonesia's zakat management. The results show that the coordination and digitalization of zakat management in Indonesia have improved, as indicated by the National Zakat Index and Digital-Readiness Index. However, there are still areas that need improvement, such as the integration of the zakat database, and the preparation of high-skilled amil or human resources in zakat management who can cope with information technology development to enhance zakat operational activities. This study highlights the importance of improving coordination and digitalization in zakat management to achieve the full potential of zakat in poverty alleviation in Indonesia.